A typology of people who tamper with pharmaceutical opioids: responses to introduction of a tamper‐resistant formulation of controlled‐release oxycodone†. (30th September 2015) - Peacock, Amy; Degenhardt, Louisa; Larance, Briony; Cama, Elena; Lintzeris, Nicholas; Ali, Robert; Bruno, Raimondo
Abstract: Purpose: In April 2014, a tamper‐resistant controlled‐release oxycodone formulation was released in Australia. We aimed to determine whether there are latent classes of people who tamper with pharmaceutical opioids based on frequency of opioid and illicit drug use, the demographic and clinical profiles of these groups, and if there were changes in use and harms following the introduction. Methods: A prospective cohort of 606 people who regularly tamper with pharmaceutical opioids was interviewed January to March 2014 (Wave 1) and May to August 2014 (Wave 2). Latent class analysis identified groups based on non‐prescribed opioid, illicit drug and prescribed opioid substitution therapy (OST) use at Wave 1. Regression models examined whether group membership predicted use and harms at Wave 2. Results: Four groups were identified: frequent OST group (39%), mixed OST / heroin group (7%), infrequent pharmaceutical opioid and heroin group (44%) and frequent oxycodone group (25%). Compared with the frequent OST group, the infrequent pharmaceutical opioid / heroin group was more likely to report non‐everyday pain and risky alcohol use, and the frequent oxycodone group had higher odds of homelessness. At Wave 2, oxycodone use decreased across groups (odds ratios (OR) ≤ 0.18, p  < 0.001, particularly for the frequent oxycodone group : OR ≤ 0.05, p  < 0.001), with reductions in days of use ( g  ≥ 0.35, p  < 0.050). Non‐prescribed pharmaceutical opioid use, illicit drug use and harms remained stable or decreased. Conclusions: Despite heterogeneity among people who tamper with pharmaceutical opioids, the tamper‐resistant formulation was followed by reductions in oxycodone tampering among high‐frequency and low‐frequency users. There was no evidence of increased use of other opioids or illicit drugs. Copyright © 2015 John Wiley & Sons, Ltd.